The Gig Economy in Different Engines of Growth: Understanding Regional Disparities in Gig Worker Quality in Bali and East Java - Putri M, Mustika; Taly Purwa (Pusat Pengembangan Kebijakan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2025)
Gig work, commonly defined as short-term, more flexible, and non-traditional employment that typically lacks formal contractual arrangements, has shaped the emergence of the gig economy and is gradually transforming labor market dynamics in Indonesia. However, research on gig workers remains limited, particularly in the context of cross-regional comparisons. This study compares the characteristics of gig workers in two regions in Indonesia with different economic structures, i.e., Bali-an economy predominantly driven by tourism-and East Java-an industry-based economy. Using data from the August 2024 National Labor Force Survey, this research employs cluster analysis to reveal the structure of gig workers in each province based on economic, socio-demographic, and technological factors, followed by multilevel regression to identify the odds for being gig workers at individual and regional levels. The findings reveal that gig workers in Bali experience relatively higher levels of wages compared to those in East Java. A similar pattern also exists for the coverage of social protection term. At the individual level, education and sector-industry and services-influence gig workers’ wages across both provinces. While at the regional level, disparities in labor market conditions and minimum wage policies contribute to differences in wage levels. These findings strengthen the understanding of gig economy dynamics across regions with different economic bases, providing valuable policy and strategic insights on expanding social protection and enhancing the use of technology to support the sustainability of labor markets in the digital era.